2004
DOI: 10.1074/jbc.m308625200
|View full text |Cite
|
Sign up to set email alerts
|

SU1498, an Inhibitor of Vascular Endothelial Growth Factor Receptor 2, Causes Accumulation of Phosphorylated ERK Kinases and Inhibits Their Activity in Vivo and in Vitro

Abstract: SU1498, an inhibitor of vascular endothelial growth factor receptor 2, has been used successfully to study the physiological manifestations of receptor functions. Here we report that in addition to its anti-receptor activity, SU1498 stimulates accumulation of phosphorylated ERKs in human umbilical vein endothelial cells and in human aortic endothelial cells in a manner that is dependent on the functioning of the upstream components of the MAPK pathway, B-Raf, and MEK kinases. The enhanced accumulation of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…4C). Although SU1498 is reported to inhibit not only Flk1 downstream kinase activation but also other receptor tyrosine kinases (PDGF, EGF, or FGF), SU1498 still strongly inhibits on VEGF-A signaling cascade (Boguslawski et al, 2004). This later result suggests that neural precursor cells in neurosphere culture release endogenous VEGF-A and that this endogenous VEGF-A facilitates neurosphere formation.…”
Section: Addition Of Vegf-mentioning
confidence: 53%
“…4C). Although SU1498 is reported to inhibit not only Flk1 downstream kinase activation but also other receptor tyrosine kinases (PDGF, EGF, or FGF), SU1498 still strongly inhibits on VEGF-A signaling cascade (Boguslawski et al, 2004). This later result suggests that neural precursor cells in neurosphere culture release endogenous VEGF-A and that this endogenous VEGF-A facilitates neurosphere formation.…”
Section: Addition Of Vegf-mentioning
confidence: 53%
“…However, it has been reported that SU1498 stimulates accumulation of phosphorylated ERKs in HUVECs and in human aortic endothelial cells, but the inhibitor blocked the kinase activity of phospho-ERK both in a direct assay and in immunoprecipitates. These findings reveal a novel and unique way in which MAPK signaling pathway may be blocked by SU1498 in human endothelial cells [35]. The effects of genistein on neovascularization, VEGF, and hypoxia inducible factor 1a (HIF-1a) protein expression in a mouse model of oxygen-induced retinopathy were studied.…”
Section: Discussionmentioning
confidence: 99%
“…7C, bars 1 and 3). SU1498 is known to block extracellular signal-regulated kinase (ERK) signaling, which might contribute to its inhibitory effect on control cells (4). However, the addition of SU1498 to PRH KD cells abolishes the growth-stimulatory effect of PRH KD and reduces the number of KD cells to around the same level seen after treatment of the control cells (Fig.…”
Section: Prh Repressesmentioning
confidence: 99%